2023
DOI: 10.1038/s41598-023-28377-7
|View full text |Cite
|
Sign up to set email alerts
|

Second-life battery systems for affordable energy access in Kenyan primary schools

Abstract: As the world transitions to net zero, energy storage is becoming increasingly important for applications such as electric vehicles, mini-grids, and utility-scale grid stability. The growing demand for storage will constrain raw battery materials, reduce the availability of new batteries, and increase the rate of battery retirement. As retired batteries are difficult to recycle into components, to avoid huge amounts of battery waste, reuse and repurposing options are needed. In this research, we explore the fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A further study proves that the battery's second life can accelerate the electrification process by reducing the costs of EVs upfront [166]. A recent paper published by Nature [167] revealed that integrating SLBs significantly reduced the cost of electricity by 5.6 % to 35.3% in most cases compared to using new batteries. Using SLBs also speeds up the time it takes for the system to pay for itself, making it financially beneficial.…”
Section: Techno-economic Challengesmentioning
confidence: 88%
“…A further study proves that the battery's second life can accelerate the electrification process by reducing the costs of EVs upfront [166]. A recent paper published by Nature [167] revealed that integrating SLBs significantly reduced the cost of electricity by 5.6 % to 35.3% in most cases compared to using new batteries. Using SLBs also speeds up the time it takes for the system to pay for itself, making it financially beneficial.…”
Section: Techno-economic Challengesmentioning
confidence: 88%
“…The other option is a second application in SLB [10,11]. An SLB can be applied to semior entirely stationary systems to store energy from solar and wind-solar farms [12][13][14].…”
Section: Introductionmentioning
confidence: 99%